Transformer Models for Recommending Related Questions in Web Search - Mitra, Rajarshee; Gupta, Manish; Dandapat, Sandipan (2020 Conference on Information and Knowledge Management, 2020)
People Also Ask (PAA) is an exciting feature in most of the leading search engines which recommends related questions for a given user query, thereby attempting to reduce the gap between user's information need. This helps users in diving deep into the topic of interest, and reduces task completion time. However, showing unrelated or irrelevant questions is highly detrimental to the user experience. While there has been significant work on query reformulation and related searches, there is hardly any published work on recommending related questions for a query. Question suggestion is challenging because the question needs to be interesting, structurally correct, not be a duplicate of other visible information, and must be reasonably related to the original query. In this paper, we present our system which is based on a Transformer-based neural representation, BERT (Bidirectional Encoder Representations from Transformers), for query, question and corresponding search result snippets. Our best model provides an accuracy of 81%.